2007
DOI: 10.1111/j.1600-6143.2006.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Donation after Cardiac Death Kidneys with Low Severity Pre-Arrest Acute Renal Failure

Abstract: The widening gap between supply and demand for renal transplantation has prompted many centers to use donors after cardiac death. Some of these donors exhibit signs of acute renal failure (ARF) prior to cardiac arrest. Concern has been expressed about poor quality of graft function from such donors. In response to this perception, we reviewed 49 single renal transplant recipients from category III donors after cardiac death between 1998 and 2005, at out center. All kidneys but one had hypothermic machine perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Recent expansion of deceased donors have been due to increased utilization of “marginal” kidneys procured from ECD, DCD, and AKI donors . Unfortunately, with liberalization of deceased donor criteria, the number of kidneys recovered with the intent to transplant and then ultimately discarded each year has nearly doubled .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent expansion of deceased donors have been due to increased utilization of “marginal” kidneys procured from ECD, DCD, and AKI donors . Unfortunately, with liberalization of deceased donor criteria, the number of kidneys recovered with the intent to transplant and then ultimately discarded each year has nearly doubled .…”
Section: Discussionmentioning
confidence: 99%
“…Although regional and national sharing may provide the opportunity to place these kidneys at centers that are willing to transplant them, longer CIT may become a confounding factor. Both longer CIT and elevated terminal donor SCr have been identified in the past as strong independent risk factors for reduced graft survival and DGF . Until recently, the combined effect of these aggravating factors was believed to be a valid reason for kidney discard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant difference in delayed graft function (DGF) and rejection rates between the two groups. Sohrabi et al [32] concluded that low severity ARF in kidneys from controlled DCD can be a reversible condition after transplantation. It is noteworthy that all but one of those kidneys had hypothermic machine perfusion and viability testing prior to transplantation.…”
Section: Now Even More Extended Criteria Kidneysmentioning
confidence: 99%
“…The major concern with such donors is about the expected poor quality of graft function. Sohrabi et al [32] reviewed 49 single renal transplant recipients from category Ⅲ donors after cardiac death between 1998 and 2005, at Newcastle, United Kingdom. According to the RIFLE criteria (risk, injury, failure, loss and end stage renal disease) [33] , nine of these recipients had kidneys from donors with "low severity pre-arrest ARF".…”
Section: Now Even More Extended Criteria Kidneysmentioning
confidence: 99%